A new complex intermetallic phase in the system Al–Cu–Ta with familiar clusters and packing principles. Issue 3 (26th February 2016) - Dshemuchadse, Julia; Bigler, Sandro; Simonov, Arkadiy; Weber, Thomas; Steurer, Walter
Abstract : The structure of hP 386‐Al57.4 Cu3.6 Ta39.0 was determined by single‐crystal X‐ray diffraction analysis. It can be described as a hexagonal close‐packing of two types of endohedral fullerene‐like clusters with different Frank–Kasper polyhedra filling the gaps. The description of the structure as a superstructure and as a layered structure illustrates other characteristic structural building principles. The diffuse scattering, which can be observed in some of the crystals, is qualitatively well reproduced by a disorder model. A comparison with the structures of the other complex intermetallics in the system Al–Cu–Ta indicates the decisive role that Cu plays in the constitution and packing of the clusters.